2017
DOI: 10.1186/s13068-017-0789-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trichoderma reesei mitogen-activated protein kinases (MAPKs) in cellulase formation

Abstract: BackgroundDespite being the most important cellulase producer, the cellulase-regulating carbon source signal transduction processes in Trichoderma reesei are largely unknown. Elucidating these processes is the key for unveiling how external carbon sources regulate cellulase formation, and ultimately for the improvement of cellulase production and biofuel production from lignocellulose.ResultsIn this work, the role of the mitogen-activated protein kinase (MAPK) signal transduction pathways on cellulase formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 67 publications
1
52
1
2
Order By: Relevance
“…In the T. reesei database ( http://genome.jgi-psf.org/Trire2/Trire2.home.html ), three genes are annotated to encode MAPK pathway members ( tmk1, tmk2, and tmk3) . Recent reports have shown that tmk2, tmk1 , and tmk3 signaling pathways may control different processes in this fungus, including cell wall integrity, cellulase production, biomass accumulation, sporulation, and resistance to high osmolarity 24 , 28 30 , however, these studies only examined the expression of a small number of genes. In the current study, we conducted a RNA sequencing-based global gene expression analysis to reveal the functions of TMK1 and TMK2 in T. reesei .…”
Section: Introductionmentioning
confidence: 99%
“…In the T. reesei database ( http://genome.jgi-psf.org/Trire2/Trire2.home.html ), three genes are annotated to encode MAPK pathway members ( tmk1, tmk2, and tmk3) . Recent reports have shown that tmk2, tmk1 , and tmk3 signaling pathways may control different processes in this fungus, including cell wall integrity, cellulase production, biomass accumulation, sporulation, and resistance to high osmolarity 24 , 28 30 , however, these studies only examined the expression of a small number of genes. In the current study, we conducted a RNA sequencing-based global gene expression analysis to reveal the functions of TMK1 and TMK2 in T. reesei .…”
Section: Introductionmentioning
confidence: 99%
“…In T. reesei , different signaling pathways have been described to be involved with fungal development and environment sensing. Among these, the signaling pathways dependent on G protein, cAMP, Ras-GTPases, protein kinases, phosphatases, calcium, and MAPK are the mostly characterized intracellular pathways although some aspects remain unclear [ 95 104 ]. Several studies showed the involvement of G α proteins in the regulation of cellulase gene transcription by light [ 105 , 106 ].…”
Section: Signaling Pathways Involved In Cellulose Sophorose Glucmentioning
confidence: 99%
“…Moreover, it was shown that the disruption of cre1 in T. reesei, or its replacement with a cre1 mutant, inhibits biomass accumulation and leads to a decrease in cellulase production (Nakari-Setä lä et al, 2009;Wang et al, 2019). Furthermore, it was reported that CCR is achieved with the phosphotransferase system (Wang et al, 2017;Liu et al, 2020). Post-translational modifications, especially phosphorylation, of the proteins involved, including Cre1, play an essential role in signal transduction to achieve CCR (Jiang et al, 2018;Horta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%